Antioxidant Mitoquinone Alleviates Chronic Pancreatitis via Anti-Fibrotic and Antioxidant Effects - Li M; Yuan Y; Han X; Liu X; Zhang W; Hao J (Dove Medical Press, 2022)
Miaomiao Li,1,* Yue Yuan,1,* Xue Han,2 Xinjuan Liu,1 Weizhen Zhang,2 Jianyu Hao1 1Department of Gastroenterology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People's Republic of China; 2Department of Physiology and Pathophysiology, Peking University Health Science Center, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianyu Hao, Department of Gastroenterology, Beijing Chao-Yang Hospital, Capital Medical University, No. 8, South Road of Workers Stadium, Chaoyang District, Beijing, 100020, Email haojianyu@ccmu.edu.cn Weizhen Zhang, Department of Physiology and Pathophysiology, Peking University Health Science Center, No. 38, Xueyuan Road, Haidian District, Beijing, 100191, Email weizhenzhang@bjmu.edu.cnBackground: Chronic pancreatitis (CP) is a long-term inflammatory disease of the pancreas that can be caused by various pathogenic factors. Oxidative stress (OS), which is associated with several pancreatic diseases, can induce pancreatic stellate cell (PSC) activation, leading to pancreatic fibrosis. Given the inefficacy of existing treatments for CP, in this study, our objective was to evaluate the therapeutic effect of the antioxidant, mitoquinone (MitoQ).Methods: First, in vivo, we established a CP mouse model via the repeated injection of cerulein. Mice in the MitoQ group simultaneously received MitoQ daily. After 4 weeks of cerulein injection, pancreatic tissues from mice were evaluated by morphological changes and the expression of fibrosis markers. Further, OS in the collected pancreatic tissue samples was evaluated by determining the level of malondialdehyde (MDA) as well as the expression levels and activities of antioxidants. Furthermore, in vitro, the effect of MitoQ on human PSCs (hPSCs) was evaluated based on PSC activation markers and fibrotic phenotypes, and OS in these treated hPSCs was evaluated by measuring reactive oxygen species (ROS), MDA, and antioxidant levels.Results: In vivo, MitoQ alleviated pancreatic fibrosis and inhibited OS in the cerulein-induced murine CP model. In vitro, it inhibited PSC activation as well as the subsequent development of the profibrogenic phenotypes by balancing out the levels of free radicals and the intracellular antioxidant system.Conclusion: MitoQ is a potential candidate for CP treatment.Keywords: chronic pancreatitis, pancreatic stellate cells, pancreatic fibrosis, oxidative stress, mitochondria-specific antioxidant, MitoQ, superoxide dismutase